Bilge Kağan Hazinesinin Gün Yüzüne Çıkarılması: Bilge Kağan Anıt Alanı Kazı Çalışmaları - Kürşat KOÇAK; L. Gürkan GÖKÇEK (Gazi Akademik Bakış)
The Göktürk goverment declared independence in 682 in the leadership of Kutlug and Tonyukuk after 40 years captivity following the collapse in 634 because Bilge Kağan and Kül Tigin were at small ages Kapgan Kağan’s ascended the throne after Kutlug Kağan’s death. Later İnel Kağan inherited the throne. Bilge Kağan and Kül Tigin came to power by staging a coup in 716. After Tonyukuk and Kül Tigin died, Bilge Kağan got poisoned and died in 734. The memorial lands were made for Kül Tigin and Bilge Kağan’s memory. Lumir Jisl dug Kül Tigin’s monument square and found note worthy information. But Bilge Kağan’s monument square has not been dug. Turks made a project about reperation and prevention of Orkun tablets and other Turkish masterpieces in Mongolia in 2000. To that end, twenty five scientists, deported from Turkey in 19th June 2000, arrived at Orkun. Archeolojical excavations in 2000 as a part of MOTAP Project were pursued by Turkish archeological excavators in Mongalia until 2004. It was searced mainly the surface in July and August. The sculptures depicting Bilge Kağan an his wife, and other sculptures except from the tablets around Kül Tigin’s monument site were put under protection by TİKA. Later in 2001, 2002, 2003 and 2004 the excavations were carried on and the baseline of the construction was unearthed. According to this, monument was constructed in around 36x72 cm rectangle site. The monument site of Bilge Kağan included an enterance gate with the marble sculptures of two bucks looking at each other’s face in a square land.